The Potential Role of C4 MYH11+ Fibroblasts and the MDK-SDC2 Ligand-Receptor Pair in Lung Adenocarcinoma: Implications for Prognosis and Therapeutic Strategies - Hongling Jia; Yanjie Bian; Jie Yuan; Yi Zhang; Shengyi Zhang (Translational Oncology)
Background: Lung adenocarcinoma (LUAD) posed a significant threat to global human health. This study employed single-cell RNA sequencing (scRNA-seq) to analyze transcriptomic data from nine LUAD patients at different stages of tumor infiltration, aiming to elucidate the tumor microenvironment and key biological processes of LUAD. Methods: In this study, we processed the scRNA-seq data using the Seurat package and sequentially applied principal component analysis followed by the Harmony package to effectively correct for batch effects, identifying 105,725 high-quality cells. Through cell clustering and gene expression profiling, we identified critical cell subpopulations and gene expression patterns in LUAD patients. Results: Our analysis revealed that the C4 MYH11+ Fibroblasts subtype was primarily involved in biological processes related to muscle function. Further investigations uncovered the MDK-SDC2 ligand-receptor pair as a critical regulator of tumor cell invasion, proliferation, and migration, driving LUAD progression. Additionally, we developed a gene-based prognostic model that effectively predicted patient survival, providing valuable clinical insights. Conclusion: This study provided a comprehensive atlas of the LUAD tumor microenvironment, highlighted the role of the C4 MYH11+ Fibroblasts in tumor progression. It also proposed the MDK-SDC2 ligand-receptor pair as a novel mechanism, addressing a significant gap in this area of research. And presented a gene-based prognostic model as a novel perspective for research into immunotherapy and drug sensitivity in LUAD.